Effects Of Temperature Stress On Symbiodinium Spp. From Selected Scleractinians - Kamphol, Nadthikphorn (2018)
Symbiodinium is described as a coccoid yellow-brown endo-symbiont, which inhabits coral tissues and provides photosynthetic products necessary for corals. However, under stressful conditions such as temperature change, the symbiotic relationship between Symbiodinium and corals may collapse and result in coral bleaching. Hence, this study was conducted to record coral species found in Pulau Songsong, Pulau Kendi and Pulau Redang, and to investigate the effects of temperature increased on the Symbiodinium cell density and health among coral species. Ten families with a total of 21 coral species were recorded. Diving-Pulse Amplitude Modulation (PAM) was used to determine the maximum quantum yield values (dark-adapted) (Fv/Fm), which is an indicator that helps to assess the current health status of corals. The in-situ Fv/Fm value of Porites somaliensis, Porites lutea, Goniopora cellulosa, Turbinaria mesenterina, Oulastrea crispata, Cyphastrea chalcidicum, Goniastrea retiformis and Pavona danai indicated that these corals were healthy and had adapted to maximum bottom light condition (600μmol quanta m-2s-1) during sampling day. Massive meandroid coral colonies like Coelastrea aspera and Goniopora cellulosa recorded high in its zooxanthellae density, 0.258±0.134x10-5cm-2, and 0.224±0.229x10-5cm-2, respectively, in 40-60mg/L total suspended solids (TSS) of turbid water area. Moreover, thermal stress experiments were conducted to investigate how the zooxanthellae thrive at 31°C to 37°C of water temperature.